Monocular vision-based displacement sensing for shunting truck guidance - Schreiber, Leon Amos (Stellenbosch University, 2025)
Schreiber, L. A. 2025. Monocular Vision-based Displacement Sensing for Shunting Truck Guidance. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/691b8e29-5ebd-46b3-a74d-0f1834193a59